A Novel Homozygous PKP2 Variant in Severe Neonatal Non-compaction and Concomitant Ventricular Septal Defect: A Case Report - Poomiporn Katanyuwong; Arthaporn Khongkraparn; Duangrurdee Wattanasirichaigoon (Frontiers Media S.A., 2022)
Left ventricular non-compaction (LVNC) is a rare and genetically heterogeneous cardiomyopathy. The disorder vastly affects infants and young children. Severe neonatal LVNC is relatively rare. The prevalence of genetic defects underlying pediatric and adult-onset LVNC is about 17-40%. Mutations of MYH7 and MYBPC3 sarcomeric genes are found in the vast majority of the positive pediatric cases. PKP2 encodes plakophilin-2, a non-sarcomeric desmosomal protein, which has multiple roles in cardiac myocytes including cell-cell adhesion, tightening gap junction, and transcriptional factor. Most of the reported PKP2 mutations are heterozygous missense and truncating variants, and they are associated with an adult-onset autosomal dominant disorder, namely arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C). Homozygous PKP2 mutations have been rarely described. Herein, we present a rare case of an infant with neonatal onset of congestive heart failure owing to severe LVNC and multiple muscular VSD. Medical treatments failed to control the heart failure and the patient died at 11 months of age. Whole-exome sequencing identified a novel homozygous PKP2 variant, c.1511-1G>C, in the patient. An mRNA analysis revealed aberrant transcript lacking exon 7, which was predicted to cause a frameshift and truncated peptide (p.Gly460GlufsTer2). The heterozygous parents had normal cardiac structures and functions as demonstrated by electrocardiogram and echocardiography. Pathogenic variants of sarcomeric genes analyzed were not found in the patient. We conducted a literature review and identified eight families with biallelic PKP2 mutations. We observed that three families (our included) with null variants were linked to lethal phenotypes, while homozygous missense mutations resulted in less severe manifestations: adolescent-onset ARVD/C and childhood-onset DCM. Our data support a previous notion that severe neonatal LVNC might represent a unique entity and had distinct genetic spectrum. In conclusion, the present study has extended the phenotypes and genotypes of PKP2-related disorders and lethal LVNC.